PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Nay Coffee and Space di Kota Surabaya) - Hartono, Antonius Dimas Joko (Seminar Nasional Ilmu Terapan, 2024)
This study aims to explore the impact of product quality, service quality, and price on customer satisfaction at Nay Coffee and Space, located in Surabaya. The population for this research consists of all visitors to the café. Sampling was conducted using the Cochran formula, resulting in 97 respondents as the study sample. To analyze the data, partial multiple regression analysis was performed using SPSS for Windows version 22. The results indicate that, simultaneously, product quality, service quality, and price have a significant effect on customer satisfaction. However, the partial testing results show that product quality does not have a significant impact on customer satisfaction. Conversely, service quality and price were found to have a significant positive effect on customer satisfaction. These findings provide valuable insights for the management of Nay Coffee and Space, allowing them to leverage this information to enhance service quality and pricing strategies to improve customer satisfaction. By focusing on these aspects, Nay Coffee and Space is expected to strengthen customer loyalty and support their business growth in the future.